The Noken System and Distorted Political Participation in Lanny Jaya’s 2024 Regional Election - Antonita Asriani Lensru; Armin Arsyad; Gustiana Kambo; Ratna Istianah (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2025)
This study analyzes the implementation of the Noken System in the 2024 Lanny Jaya Regency Head and Deputy Regency Head Elections and its impact on the political participation of indigenous Papuans. The Noken System, as a collective voting practice based on local wisdom, has gained constitutional legitimacy through Constitutional Court Decision Number 47-81/PHPU.A-VII/2009. However, its implementation creates a paradox between the principle of electoral democracy, which emphasizes individual voting rights, and the tradition of communal deliberation among indigenous peoples. This study uses a qualitative approach with a case study method, collecting data through in-depth interviews, participatory observation, and document analysis. The results show that the Noken System in Lanny Jaya Regency has undergone a transformation from a traditional deliberation mechanism to a political mobilization tool that is vulnerable to politicization and elite intervention. The role of the Big Man as the determinant of collective choice has shifted from traditional legitimacy to a transactional patronage-client relationship. This study found three patterns of political participation, such as authentic communal participation based on customary consensus, participation guided by elites, and transactional participation involving material exchanges. This study contributes to the theory of legal pluralism and deliberative democracy by revealing the complexity of negotiations between state law and customary law in the context of Indonesian electoral democracy.